Enhancing supercapacitor energy density by mass-balancing of graphene composite electrodes. (10th November 2020) - Redondo, Edurne; Fevre, Lewis W. Le; Fields, Richard; Todd, Rebecca; Forsyth, Andrew J.; Dryfe, Robert A.W.
Highlights: Energy-based optimisation of graphene additives for supercapacitor electrodes. Operating voltage window increased to 3.2 V. Energy density of optimised cells is double that of symmetric, non-graphene cells. Abstract: We present a new strategy to optimise the energy density of supercapacitor cells, by systematically varying the amount of graphene-related additive, while mass balancing the positive and negative electrodes. The capacitance and the electrochemically stable potential window of the electrodes have been determined for several electrodes with different additive loadings by using a recently reported electrode optimisation technique. These key factors for calculating the mass balance were obtained based on the constant current charge/discharge cycling with a coin-cell-incorporated quasi-reference electrode. Then, multi-pairing of electrodes is proposed based on the maximum theoretical energy density, and optimised supercapacitor cells have been assembled. Using this strategy, these cells are shown to reach a voltage of 3.2 V within stability conditions, providing an energy density of 37.9 W h kg −1 (double the value for a symmetric non-graphene cell) and a power density of 149 kW kg −1 at 2 A g −1, using 1 M tetraethylammonium tetrafluoroborate (TEABF4 ) in acetonitrile as the electrolyte, placing these cells in between traditional and hybrid supercapacitors.